Implementasi Permainan Edukatif Upcycle Kardus Untuk Penanaman Nilai Karakter Melalui Media Pembelajaran Hak dan Kewajiban Pada Anak di Rubbik School Semarang - Arif, Dwi Muhammad; Sari, Maria Anita; Diana, Asna; Silviana, Silviana; Karim, Abdul (Faculty of Teacher Training and Education of Undaris, 2025)
This research is motivated by the assignment of the Leadership Project course for students of thePPG Teacher Candidate study program at FKIP Ivet University which is carried out at Rubbik SchoolSemarang, a private institution that facilitates children from underprivileged families, dropping out of school,and busking, because they want to help their parents' economy. The presence of students to implementeducational games upcycle cardboard for instilling character values through learning media for rights andobligations in children at rubbik school.Descriptive qualitative research method that describes the implementation of educational games toinstill religious, honest, disciplined and caring characters through learning media rights and obligations.The results of the study show that in instilling religious character, children are accustomed to praying beforedoing activities and being grateful after completing them, especially in carrying out worship. Honestcharacter, the existence of harmony between words and actions so that it is expected to become a person whois trusted by others. Disciplined character, consistently implementing all forms of rules or regulationswherever they are. Caring character, instilling attitudes and actions that reflect concern for other peopleand communities in need.Keywords: Educational games, character values, learning media